Analisis Pengetahuan Ibu dan Status Gizi terhadap Tumbuh Kembang Anak Usia 12 – 36 Bulan di Wilayah Kerja Puskesmas Tinggede Kabupaten Sigi - Sri Utami Ningsih; Yenny Puspitasari; Yuly Peristiowati (Universitas Malahayati, 2026)
ABSTRACT According to Rambe Sebayang, 22.5% of children in Argentina experience developmental problems, 12%-16.6% in the United States, 24% in Thailand, and 13%-18% in Indonesia. The prevalence of developmental delays in Indonesia is around 5-10%. One in 100 children has low intelligence and speech delays, two in 1,000 babies experience motor development disorders, and 3-6 in 1,000 babies also experience hearing disorders. Based on the results of the 2022 Indonesian Nutritional Status Study (SSGI), the national prevalence of stunting was 21.6%, wasting 7.7%, and underweight 17.1%. Meanwhile, based on the 2023 health profile data for Central Sulawesi Province, the prevalence of nutritional status of toddlers aged 0-59 months with low body weight (BB/U) in Sigi Regency was 15.4% of children experiencing malnutrition. The purpose of this study was to analyze the influence of maternal knowledge and nutritional status on the growth and development of children aged 12-36 months in the Tinggede Community Health Center, Sigi Regency. This study uses an observational design with a cross-sectional approach. Respondents were taken using a purposive sampling technique. The population is all children aged 12-36 months in the Tinggede Community Health Center working area, Sigi Regency. The sample size is 103. The independent variables are maternal knowledge and nutritional status. The dependent variable is child growth and development. Statistical tests use logistic regression tests. The influence of nutritional status on child growth and development with a significance value of 0.002 and an odds ratio value of 25.847, the influence of maternal knowledge on child growth and development with a significance value of 0.001 and an odds ratio value of 36.194. Meanwhile, the most influential factor on child growth and development is knowledge with an odds ratio value of 36.194. Knowledge and nutritional status influence the growth and development of children aged 12-36 months in the Tinggede Community Health Center working area, Sigi Regency. Keywords: Knowledge, Nutritional Status, Growth And Development. ABSTRAK Menurut Rambe Sebayang anak yang mengalami masalah tumbuh kembang di Argentina 22,5%, Amerika serikat 12%-16,6%, Thailand 24% dan Indonesia 13%-18%. Prevalensi keterlambatan tumbuh kembang di Indonesia sekitar 5−10 %. Satu dari 100 anak mempunyai kecerdasan kurang dan keterlambatan bicara, dua dari 1.000 bayi mengalami gangguan perkembangan motorik dan 3-6 dari 1.000 bayi juga mengalami gangguan pendengaran. Berdasarkan hasil Studi Status Gizi Indonesia (SSGI) tahun 2022 melaporkan prevalensi stunting secara Nasional 21,6%, Wasting 7,7%, dan underweight 17,1%. Sedangkan berdasarkan data profil kesehatan Provinsi Sulawesi Tengah Tahun 2023 menunjukkan prevalensi status gizi balita 0-59 bulan dengan berat badan kurang (BB/U) di Kabupaten Sigi sebanyak 15,4 % anak mengalami gizi kurang. Tujuan penelitian ini untuk menganalisis pengaruh Pengetahuan Ibu Dan Status Gizi Terhadap Tumbuh Kembang Anak Usia 12 – 36 Bulan Di Wilayah Kerja Puskesmas Tinggede Kabupaten Sigi. Penelitian ini menggunakan desain observasional dengan pendekatan Crossectional. Responden di ambil dengan teknik purposive sampling. Populasi Semua Anak usia 12 – 36 bulan Di wilayah kerja Puskesmas Tinggede Kabupaten Sigi. Besar sampel sebanyak 103. Variabel independen yaitu Pengetahuan ibu dan status gizi . Variabel dependen yaitu Tumbuh Kembang anak. Uji statistik menggunakan uji Regresi logistik. Pengaruh status gizi Terhadap Tumbuh Kembang Anak dengan nilai signifikansi sebesar 0,002 dan nilai Odds rasio sebesar 25,847, pengaruh Pengetahuan Ibu Terhadap Tumbuh Kembang Anak dengan nilai signifikansi sebesar 0,001 dan nilai Odds rasio sebesar 36,194. Sedangkan yang paling berpengaruh terhadap tumbuh kembang anak yaitu pengetahuan dengan nilai Odds rasio sebesar 36,194. Pengetahuan dan status gizi berpengaruh Terhadap Tumbuh Kembang Anak Usia 12 – 36 Bulan Di Wilayah Kerja Puskesmas Tinggede Kabupaten Sigi Kata Kunci: Pengetahuan, Status Gizi, Tumbuh Kembang.